IQuant: An automated pipeline for quantitative proteomics based upon isobaric tags - Wen, Bo; Zhou, Ruo; Feng, Qiang; Wang, Quanhui; Wang, Jun; Liu, Siqi (Proteomics (Weinheim), 2014)
Quantitative proteomics technology based on isobaric tags is playing an important role in proteomic investigation. In this paper, we present an automated software, named IQuant, which integrates a postprocessing tool of protein identification and advanced statistical algorithms to process the MS/MS signals generated from the peptides labeled by isobaric tags and aims at proteomics quantification. The software of IQuant, which is freely downloaded at http://sourceforge.net/projects/iquant/, can run from a graphical user interface and a command‐line interface, and can work on both Windows and Linux systems.